Composite Generalized Variational Inequalities With Wiener-Hopf Equations - Khan, Zubair; Irfan, Syed Shakaib; Ahmad, Iqbal; Shukla, Preeti (Communications in Mathematics and Applications, 2020)
An introduction and study of a composite generalized variational inequality problem with a composite Wiener-Hopf equation in separable real Hilbert space is performed. Projection operator technique has been employed, to establish the equivalence between the composite generalized variational inequality problem with a composite Wiener-Hopf equation. Equivalent formulation discuss the existence of solution of the problem. Under some specific conditions, the convergence analysis of the suggested iterative algorithm has been discussed. The paper also specks that the problem and results obtained are more general than the papers that are already available in the literature.
Keywords: Algorithms; Composite variational inequalities; Composite Wiener-Hopf equation; Convergence analysis; Monotone operators